The Witch of Clan Sinclair - Ranney, Karen (New York, New York Avon, an imprint of HarperCollinsPublishers, 2014)
"Logan Harrison is looking for a wife. As the Lord Provost of Edinburgh, he needs a conventional and diplomatic woman who will stand by his side and help further his political ambitions. He most certainly does not need Mairi Sinclair, the fiery, passionate, fiercely beautiful woman who tries to thwart him at every turn. But if shes so wrong for him, why cant he stop kissing her? He is completely bewitched. Mairi Sinclair has never met anyone like Logan Harrison, the perfect example of everything she finds wrong with the world. Hes also incredibly handsome, immensely popular, and impossible to resist. His kisses inflame her and awaken a passion she can barely control. Can two people who are at such odds admit to a love that would bind them together for life?"-- From back cover.
Keywords: Women newspaper editors -- Fiction; Politicians -- Fiction; Romance fiction; Historical fiction